The European Economic and Monetary Union – between vulnerability and reform. (17th January 2012) - Blanke, Hermann-Josef
For more than two years, the global financial and economic crisis has put the European Union to one of its hardest tests. Until now, no end is foreseeable. Following the need to rescue banks and industrial companies, the rescue of indebted EU Member States is on the Union's agenda. However, the European Treaties neither provide a constitutional framework nor suitable instruments to counteract sovereign default of Member States. In 2011 the Union has to decide on a fundamental reform of its economic constitution. At its core, this is about answering the question of how the European budgetary stability mechanisms and instruments need to be set up in order to ensure a rational design of the Economic and Monetary Union and enable effective budgetary coordination. This contribution will deal with the scope of the budgetary regulatory capacity of the 'new' instruments and will analyse their interaction.